Phenotyping maize for adaptation to drought - Araus, José Luis; Serret, María Dolors; Edmeades, Greg (Frontiers in Physiology, 2012)
The need of a better adaptation of crops to drought is an issue of increasing urgency. However, enhancing the tolerance of maize has therefore proved to be somewhat elusive in terms of plant breeding. In that context, proper phenotyping remains as one of the main factors limiting breeding advance. Topics covered by this review include the conceptual framework for identifying secondary traits associated with yield response to drought and how to measure these secondary traits in practice.